Vers la structuration d’une filière aurifère « durable » ? Etude du cas de la Guyane française - Jessica Oder (EchoGéo)
The aim of this article is to wonder whether the gold mining sector, in French Guiana, can be in line with the objectives of sustainable development. Actually, this sector is in the grip of difficulties: whereas gold rates are in constant increase, the number of mining operators drops constantly, since nearly seven years. This Guianese paradox originates in the will of the French State to make gold sector an example as regards “sustainability”, as clearly expressed in the aftermath of the « Grenelle of the Environment ». Mainly based on semi-directing talks and archives, the article sought to analyze the key elements of this structuring: the project of Departmental Mining Master Plan (SDOM) and several initiatives dedicated to improve the mining operators’ practices. However, this evolution of which pace is variously appreciated, is not done without disagreements, insofar as it puts in relief antagonisms between the stakeholders (mainly territorial collectivities and the central level, operators mining and environmentalists). Indeed, these antagonisms were revealed, on the one hand, during the Camp Caiman case (which involved Iamgold), and on the other hand during the development process of the SDOM itself. Related problems such as local claims of mining governance and the illegal artisanal and small scale gold mining draw up future prospects rather mitigated for the sector.